Susceptibility of a cell line derived from the kidney of Chinese rice‐field eel, Monopterus albus to the infection of rhabdovirus, CrERV. Issue 2 (29th November 2021) - Liu, Wenzhi; Fan, Yuding; Zhou, Yong; Jiang, Nan; Li, Yiqun; Meng, Yan; Xue, Mingyang; Li, Zhong; Zeng, Lingbing
Abstract: Chinese rice‐field eels rhabdovirus (CrERV), belonging to the genus Perhabdovirus in the family Rhabdoviridae, is the causative agent of the haemorrhagic disease of Chinese rice‐field eels, Monopterus albus . The present study aims to establish a cell line derived from the kidney of Chinese rice‐field eel (CrEK) for the further study of the pathogenic virus. CrEK cells were epithelioid‐like and grew well in M199 medium supplemented with 10% foetal bovine serum at 28°C, and the cell line has been subcultured for more than 80 times. Karyotyping analysis of CrEK cells at 25th passage indicated a modal chromosome number of 24. Significant cytopathic effect (CPE) was observed in CrEK cells after infection with CrERV, and the virus titre reached 10 7.8 ± 0.45 TCID50 /mL. The transmission electron microscopy revealed that there were a large number of virus particles in the cytoplasm of cells. The virus infection in cells was also assayed by using indirect immunofluorescence assay (IFA), fluorescence in situ hybridization (FISH), reverse transcription PCR (RT‐PCR) and quantitative real‐time reverse transcription‐PCR (qRT‐PCR). In experimental infection, CrERV cultured by cells could cause over 90% mortality in fish. CrEK represents the first kidney cell line originated from Chinese rice‐field eels and be a potential material for investigating the mechanism of virus infection in this fish and the control methods for the disease.